Polysomnographic Sleep Dysregulation in Cocaine Dependence - Valladares, Edwin M. (ScientificWorldJournal, 2007)
Insomnia and sleep disturbance are associated with declines in health functioning, alongwith increases in mortality risk. Given the prominence of reported sleep disturbance incocaine-dependent subjects and persistence into recovery, understanding the natureand severity of these disturbances in this population may help to identify relevantpathways that contribute to the increased mortality in cocaine dependence. Polysomnography provides a means of objectively characterizing sleep and, in turn, sleep disturbances. Few studies have used polysomnography to evaluate sleep incocaine-dependent persons, yet these studies have the potential to advance treatmentsthat will ultimately reduce morbidity in cocaine-dependent subjects.